CONCENTRATION AND SIZE OF AIRBORNE PARTICLES IN MANUFACTURING ENVIRONMENTS - Renilson Luiz Teixeira; Raphael Nogueira Rezende; José Reinaldo Moreira da Silva; Luana Elís de Ramos e Paula (Revista Árvore, 2018)
ABSTRACT In furniture factories, the cutting of medium density fiberboard (MDF) generates high concentrations of particulates suspended in the air, which, depending on their dimensions, can reach the sensitive areas of the respiratory tract of workers. The aim of this study was to test a method to measure particle sizes derived from the cutting of wood paneling. The experiment was conducted in two small furniture factories located in the municipality of Lavras, Minas Gerais state, Brazil. During the cutting of MDF, airborne particles were collected and measured by means of optical microscopy. The data obtained showed a critical condition in the work environments, with high concentrations of small particles (<10 microns), which could be lodged in the workers’ lungs. The particle measuring process proved to be accurate and easy to perform. In addition, it is worth noting the importance of investment in personal protective equipment (PPE) such as hoods and/ or PFF2 dust masks for the protection of workers.